Insecticides can increase pest damage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Groundnut farmers in India apply so much insecticide that they end up inducing pest outbreaks. Their counterparts in Africa rarely use chemical sprays, and their crops suffer less damage from pests. Researchers at the International Crops Research...